Justifications of repression in autocracies: An empirical analysis of the Maghreb, 2000-2010 - Maria Josua (German Institute of Global and Area Studies (GIGA), 2022)
Previous studies on the justification of repression have analysed large-scale protests, about which autocratic officials communicate to avoid backlash effects. However, we know much less about how everyday repression against dissidents and ordinary citizens is communicated and justified under authoritarianism. This paper is the first to systematically investigate how officials in autocracies justify, conceal, or deny different forms of repression employed by different state institutions. It studies the communication of repression in two North African autocracies, drawing on the novel Justifications of Repressive Incidents in Morocco and Tunisia Dataset. The dataset contains 439 events between 2000-2010 and disaggregates the various dimensions of repression and its communication. The empirical analysis shows that the chosen forms of repression influence patterns of communication and justification. Studying the communication of repression helps us better understand the nexus of authoritarian legitimation and political violence in the Middle East and North Africa region and beyond.
Keywords: 300; North Africa; Maghreb; repression; legitimation; communication; justification; dataset